Is there an influence of start slope inclination on movement and force patterns in Ski Cross starts - Nedergaard, N.; Heinen, F.; Sloth, S.; Holmberg, H. C.; Kersting, U. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The purpose of this study was to investigate the start slope inclination s influence on force and movement patterns in ski cross starts.